Effects of Segmental Stabilization in Patients with Low Back Pain: Systematic Review - Nascimento, Rayane Kallyne Berto Do; Costa, Sillwe Capitulino Farias; Sales, Thiani Sousa; Silva, Rodrigo Marcel Valentim da (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Low back pain is a problem that affects a large part of the population, about 80%, reaching people with greater constancy in the period of higher productivity. For the treatment of this condition there are several physiotherapeutic techniques, among them the segmental stabilization is specific exercises for the stabilizing muscles of the lumbar spine, aiming at a better control and activation of the deep muscles. Methods: A systematic review was performed through the PubMed, Scielo, Google academic, Bireme and Medline databases. Results: After the search, the results show that the segmental stabilization exercises reduced pain, as well as improved functional capacity. Conclusion: Segmental stabilization exercises proved to be an efficient proposal for the treatment of low back pain, showing efficacy both in pain and in improving functional capacity.